Carbon Stocks in Pinus merkusii and Acacia auriculiformis Stands at Mangunan Protection Forest, Dlingo, Bantul, Special Region of Yogyakarta - Mizana Ijazah; Retno Peni Sancayaningsih (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Tropical forests have roles in storing carbon. Plant stored carbons as biomass in plant organs (roots, woods, stems and leaves). Carbon is also stored in the litter and soil organic matter. Carbon sequestration by stand or forest can reduce carbon emissions which causes global warming. This research aims to study the abundance of species of tree, sapling and seedling growthform. It also aims to estimate biomass and carbon content in the Acacia and Pine stands. This study was conducted on January-March 2015 in Protection Forest Mangunan, Dlingo, Bantul, Yogyakarta. The research consists of two stages: species abundance measurement in both stands, height and diameter measurements of  tree and sapling in stands. This study used the quadratic plot method (10 x 10 m2), which consists of 5 plots in each stand. Furthermore, data of tree height and diameter is used to estimate carbon stocks in Acacia and Pine stands. Carbon stocks calculation using allometric formula from Heriyanto et al. (2005) for Pinus merkusii and from BPKH Wil. XI and MFP II (2009) for Acacia auriculiformis. From this study it is known that in Acacia stand there are 8 species, whereas in the Pine stand there is only one species, Pinus merkusii  (density 1,160 ind/ha). The most abundant species in the tree growthform in Acacia stand  is Acacia auriculiformis (density 380 ind/ha), in the sapling growthform is Voacanga grandifloria (density  520 ind/ha) and in seedling growthform is unidentified species (density 29,600 ind/ha). Biomass and carbon content in the Acacia stand  (1172.70 ton/ha and 586.35 tC/ha) is higher than the Pine stand (884.62 ton/ha and 442.31 tC/ha). The ability carbon sequestration in Acacia stand is higher than Pine stand.Keywords: biomass, carbon stocks, Mangunan Forest